Does extreme poverty occur in EU countries? - Antošová, Irena (University of Pardubice, 2019)
Poverty as a result of income inequality is a concern for governments in all countries, including the European Union. The question is how serious the poverty is and in which households it occurs. This paper offers the identification of households at risk of extreme poverty based on the construction of the Extreme Poverty Index. This Index combines three dimensions of poverty, reflecting trends in measuring multidimensional poverty. The first component of the index is income poverty, the second is material deprivation of households, which complements the index by a non-income perspective and reflects the real living conditions of households. The third component of the index is the low work intensity of the household. Segments of households at risk of extreme poverty are identified in a cluster analysis using primary data from EU-SILC survey. These identified households should be the target groups of the social policy activities in order to make social policy and assistance to endangered households as effective as possible. The paper provides a comparison of extreme poverty in households in the Czech Republic, Germany, Poland and Slovakia. The most vulnerable segment in all countries is an unemployed pre-retirement consumer living alone, but also other household groups.
Keywords: extreme poverty; income; material deprivation; unemployment; social transfers; EU-SILC; I32; P46; D31; I31